Long‐term clinical outcomes from real‐world experience of left atrial appendage exclusion with LARIAT device. (21st October 2019) - Parikh, Valay; Bartus, Krzysztof; Litwinowicz, Radoslaw; Turagam, Mohit K.; Sadowski, Jerzy; Kapelak, Boguslaw; Bartus, Magdalena; Podolec, Jakub; Brzezinski, Maciej; Musat, Dan; Rasekh, Abdi; Mittal, Suneet; et al.
Abstract: Background: Left atrial appendage closure (LAAC) with LARIAT has emerged as one of the alternatives to oral anticoagulation (OAC) in patients with nonvalvular atrial fibrillation (AF). Our aim was to study long‐term outcomes in patients undergoing LARIAT procedure. Methods: We analyzed patients screened for LARIAT device in four centers between December 2009 and June 2012. Out of these, patients who didn't undergo LAAC with the LARIAT device due to unfavorable LAA morphology and other preprocedural contraindications were included in control group. We analyzed thromboembolism, bleeding events, and mortality between LAA and control group. Results: About 153 patients were screened. Out of these, 108 (70.6%) patients underwent LARIAT placement (LAA arm) and 45 (29.4%) excluded patients were included in control arm. There were no differences in CHADS2 and CHA2 DS2 ‐VASc score. Mean HAS‐BLED score was significantly higher in the LARIAT group (3.5 ± 1.06 vs 3.09 ± 1.22, P  = .04). Mean follow‐up time (in years) was 6.56 ± 0.84 in LAA and 6.5 ± 1.26 in control arm. During follow‐up period, the LARIAT group was associated with significantly less thromboembolic events (1.9% vs 24%, P  < .001), bleeding events (9.2% vs 24.4%, P  = .03), and mortality (5.6% vs 20%, P  = .01) as compared with the control group. Conclusions: Long‐term data from routine clinical practice from our study suggests that LAA exclusion with LARIAT device is an effective treatment in management of nonvalvular AF patients with high risk of stroke, bleeding, and mortality. Further randomized trials, such as aMAZE, will provide more insight in this expanding field.